See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches - Mironov, Alexandr N. (Zootaxa, 2019)
In the North-West Pacific hadal trenches, four species belonging to the stalked crinoid genus Bathycrinus were found, three of them are new for science: Bathycrinus kirilli n. sp., B. longipinnus n. sp. and B. rozhnovi n. sp. B. kirilli n. sp. from the Izu-Bonin Trench (9715–9735 m) is the deepest-dwelling crinoid species. Similar characters shared by B. kirilli n. sp. to B. volubilis Mironov, 2000 from the Kuril-Kamchatka Trench (8175–9584 m) related to trench topography with isolated small basins, as previously suggested by Belyaev (1989). Hypotheses explaining why deepest hadal Bathycrinus species display higher abundance than species inhabiting shallower environments are discussed.